STUDI PENGARUH VOLUME LALU LINTAS TERHADAP TINGKAT KEBISINGAN PADA RUAS JALAN TIPE 2/2 UD ( STUDI KASUS RUAS JALAN KH. AHMAD DAHLAN - ALIANDANI, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2017)
Know the level ketergangguan users public facilities associated with standard pollution levels sound allowed, according environment minister decision of Indonesia KEP-48 / MENLH / 11 / 1996. This research take cases in jalan KH. Ahmad Dahlan that is local road, located on road traffic congestion high traversed city transport and personal craft and these roads become access for students attend SMPN 2 Samarinda, islamic education foundation (Yayasan Pendidikan Islam) East Kalimantan, and SMKN 4 Samarinda.This research was intended to analyze noise level due to traffic on jan KH. Ahmad Dahlan Samarinda. Make a model mathematical state of relationship between noise level with the volume of vehicles and analyze ekivalensi noise vehicles due to traffic. Data analysis by conducting survey field, the data collected and processed then analyzed to obtain conclusion in accordance with the actual condition that is dilokasi survey.Based on the analysis and the highest level of noise vehicle on KH. Ahmad Dahlan of Samarinda with 3 points the sample collection for 24 hours in a can value of 69,86 dBA. This value surpassing quality standards for noise based on the resolution readmitted environment No. 48 years 1996 on raw noise level for the area of school and a settlement worth 55 dBA. Compared with health regulations readmitted No. 718 1987 about noise, the location of this measure should have zones C, among other offices, shops, trade, market, with noise around 50-60 dBA.